2016
DOI: 10.1038/nnano.2016.23
|View full text |Cite
|
Sign up to set email alerts
|

Aggregated single-walled carbon nanotubes attenuate the behavioural and neurochemical effects of methamphetamine in mice

Abstract: Methamphetamine (METH) abuse is a serious social and health problem worldwide. At present, there are no effective medications to treat METH addiction1. Here, we report that aggregated single-walled carbon nanotubes (aSWNTs) significantly inhibited METH self-administration, METH-induced conditioned place preference and METH- or cue-induced relapse to drug-seeking behaviour in mice. The use of aSWNTs alone did not significantly alter the mesolimbic dopamine system, whereas pretreatment with aSWNTs attenuated MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…Recently, a study reported that SWNTs (see Figure 1) could alleviate methamphetamine addiction by oxidized excessive dopamine [43]. In this study, aggregated form of SWNTs not only inhibited drug craving and relapse in mice, but also attenuated methamphetamine-induced conditioned place preference.…”
Section: Advances In the Therapeutic Effects Of Carbon Nanotubes On Msupporting
confidence: 52%
“…Recently, a study reported that SWNTs (see Figure 1) could alleviate methamphetamine addiction by oxidized excessive dopamine [43]. In this study, aggregated form of SWNTs not only inhibited drug craving and relapse in mice, but also attenuated methamphetamine-induced conditioned place preference.…”
Section: Advances In the Therapeutic Effects Of Carbon Nanotubes On Msupporting
confidence: 52%
“…295,296 Carbon nanotubes have unique properties that make them a highly promising system for biomedical application, as they can be used to deliver therapeutic drugs and diagnostic agents into cells. 297,298 However, carbon nanotubes can also absorb light in the near-infrared region as photosensitizers and can kill cancer cells by localized photothermal effects. 299 …”
Section: Ruthenium(ii)-based Nanomaterials Systemsmentioning
confidence: 99%
“…Recently, evidences in the literature have shown a strong correlation between the nature of this complex multilayer of biomolecules (often called biomolecular corona) and the cellular uptake of nanoparticles in vitro and in vivo 5678910111213. In this respect a key role is played by the organization and mutual orientation of the molecules on the nanoparticle surface.…”
mentioning
confidence: 99%